The effectiveness of specific warm-up protocol to enhance static and dynamic postural control in female team handball players - Steib, S.; Zahn, P.; Zech, A.; Pfeifer, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Lower extremity (LE) injuries are very common in team handball, especially in female athletes. The risk of sustaining a LE injury has been associated with several internal factors, including poor postural control (Willems et al. 2005). The aim of this study was to investigate the effectiveness of a specific warm-up programme to enhance static and dynamic postural control abilities in female team handball players. Methods: An adapted version of `The 11+` (Soligard et al., 2008), a warm-up programme for injury prevention in soccer, was implemented in three German female handball teams (4th division). A total of 41 players were randomized into a control (n=20, age = 24.00 ± 5.59 years, height: 168.95 ± 4.57 cm, mass: 65.90 ± 6.77 kg) and an intervention group (n=21, age: 23.95 ± 6.27, height: 171.43 ± 7.02, mass: 65.52 ± 7.69). Subjects in the intervention group (IG) carried out the adapted protocol instead of their regular warm-up routine for 11 weeks. The programme consisted of seven exercises targeted at increasing joint and trunk stability as well as postural control, and was performed prior to each training session and before competition. The control group (CG) kept their regular training regime. The main outcome measures were: COP velocity (vCOP) in single-leg-stance, mean reach distance in the `star excursion balance test` (SEBT) and the `dynamic postural stability index` (DPSI) calculated from a unilateral jump-landing task. A two factorial linear mixed model (random intercept and slope) was specified for each of the main outcomes with `group` and `time` as fixed factors. Results: No significant differences existed in group demographics at baseline. After 11 weeks of training, subjects in the intervention group significantly (p<.05) improved in the SEBT (5.6%) compared to the control group (3.6%). The same trend existed for the reduction of vCOP (IG: -16.1%, CG: - 7.1%) but this was not statistically significant. No significant changes were seen for the DPSI (IG: 2.9%, CG: -0.8%). Conclusions: A specific warm-up programme regularly incorporated prior to training and competition can be effective to enhance some aspects of postural control in female handball players.